2015
DOI: 10.1038/bjc.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free AR and CYP17A1 copy number variations may associate with outcome of metastatic castration-resistant prostate cancer patients treated with abiraterone

Abstract: Background:This study aimed to investigate copy number variations (CNVs) of CYP17A1 and androgen receptor (AR) genes in serum cell-free DNA collected before starting abiraterone in 53 consecutive patients with castration-resistant prostate cancer (CRPC).Methods:Serum DNA was isolated and CNVs were analysed for AR and CYP17A1 genes using Taqman copy number assays. The association between CNVs and progression-free/overall survival (PFS/OS) was evaluated by the Kaplan–Meier method and log-rank test.Results:Median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 31 publications
6
84
0
4
Order By: Relevance
“…Additionally, gain of CYP17A1 has been associated with reduced progression-free survival (PFS) in men receiving abiraterone treatment 14 and loss of RB1 has predicted worse PFS in men treated with enzalutamide 16 . Only a few studies have employed genome-wide approaches of plasma DNA analyses in prostate cancer 11, 13, 18, 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, gain of CYP17A1 has been associated with reduced progression-free survival (PFS) in men receiving abiraterone treatment 14 and loss of RB1 has predicted worse PFS in men treated with enzalutamide 16 . Only a few studies have employed genome-wide approaches of plasma DNA analyses in prostate cancer 11, 13, 18, 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study published by Azad et al [42] used cell-free DNA analyses from patients treated with either enzautamide or abiraterone to demonstrate that patients with an AR gene aberration, defined as copy number variation or mutation in exon 8, had poorer clinical outcomes, lower rates of PSA decline, and shorter time to progression. Another study by Salvi et al [43] demonstrated similar results when looking at AR copy number variation and mutations in the CYP17A gene in patients treated with abiraterone.…”
Section: Orteronel Galeterone and Vt-464mentioning
confidence: 58%
“…Bei Patienten mit Prostatakarzinom unter Hormontherapie konnte anhand von ctDNA-Analysen eine Assoziation zwischen dem Vorliegen von bestimmten SCNAs und dem klinischen Outcome gezeigt werden [105]. Die vermehrte Entstehung von fokalen Amplifikationen in fortgeschrittenen Stadien, was auf eine hohe Plastizität der Tumore hindeutet, konnte von uns kürzlich aus dem Plasma nachgewiesen werden [80].…”
Section: Bedeutung Von Genomweiten Analysenunclassified